Effect of Cigarette Smoking on Fasting Serum Glucose in Healthy Male Population (Community Based Medical Journal, 2019)
Acute effects of cigarette smoking include impaired insulin action that leads to abnormal glucose metabolism. Smoking is an independent risk factor for type 2 diabetes which is one of the global health crises and insulin resistance is one of the main risk factors for cardiovascular disease. This cross-sectional study was done to examine whether fasting serum glucose differs between cigarette smokers compared to non-smokers and to investigate the association of cigarette smoking with the development of impaired fasting glucose and type 2 diabetes. This study was done in the Physiology department of Mymensingh Medical College, an outpatient department of Mymensingh Medical College Hospital, for over a period of one year from July 2014 to June 2015. Fasting serum blood glucose was done by enzymetric colorometric GOD-PAP method in a total of 150 subjects, in which non-smokers were 50 and numbers of smokers were 100 with the duration of smoking 5 - 10 years and >10 years. A questionnaire including data was completed in all cases. The data were checked, coded, and entered into an SPSS 11.5. Statistical significance of difference among the groups was calculated by Students unpaired t' test. P-value